β1‐receptor polymorphisms and junctional ectopic tachycardia in children after cardiac surgery - Leanne Dumeny; Marut Chantra; Taimour Langaee; Benjamin Q. Duong; Daniel H. Zambrano; Frank Han; Dalia Lopez‐Colon; James F. Humma; Jonathan Dacosta; Tommie Lovato; Connie Mei; Julio D. Duarte; et al. (Wiley, 2022)
Abstract Junctional ectopic tachycardia (JET) is a potentially life‐threatening postoperative arrhythmia in children with specific congenital heart defects and can contribute significantly to postoperative morbidity for at‐risk populations. In adults, β1‐adrenergic receptor (ADRB1) and β2‐adrenergic receptor (ADRB2) genotypes have been associated with increased risk for arrhythmias. However, their association with arrhythmia risk in children is unknown. We aimed to test associations between ADRB1 and ADRB2 genotypes and postoperative JET in patients with congenital heart defects. Children who underwent cardiac surgery were genotyped for the ADRB1 p.Ser49Gly (rs1801252; c.145A>G), p.Arg389Gly (rs1801253; c.1165C>G), ADRB2 p.Arg16Gly (rs1042713; c.46A>G), and p.Glu27Gln (rs1042714; c.79G>C) polymorphisms. The occurrence of postoperative JET was assessed via cardiologist‐interpreted electrocardiograms. Genotype associations with JET were analyzed via logistic regression, adjusted for clinical variables associated with JET, with separate analysis in patients not on a β‐blocker. Of the 343 children included (median age 8 months, 53% boys, 69% European ancestry), 45 (13%) developed JET. The Arg389Arg genotype was not significantly associated with JET in the overall population (odds ratio [OR] = 1.96, 95% confidence interval [CI] = 0.96-4.03, p = 0.064), but was nominally associated in patients not taking a β‐blocker (n = 324, OR = 2.25, 95% CI = 1.05-4.80. p = 0.034). None of the other variants were associated with JET. These data suggest that the ADRB1 Arg389Arg genotype may predict risk for JET following cardiac surgery in pediatric patients in the absence of β‐blockade. Whether treatment with a β‐blocker ameliorates this association requires further research.